HUBUNGAN TINGKAT ADIKSI INTERNET DENGAN DERAJAT DEPRESI MAHASISWA PREKLINIK FAKULTAS KEDOKTERAN - Aristia, Lintang Briliana; Manafe, Derri Tallo; Kareri, Dyah Gita Rambu; Trisno, Idawati (Universitas Nusa Cendana, 2022)
Background: Internet in the millennium era is used as a tool for exchanging information and a media for communication on a large scale, therefore it becomes a necessity in our daily life. According to the Indonesian Internet Service Users Association (APJII), the largest number of internet users in Indonesia are students, including medical students, compared to adolescents and the general population. There are many conveniences offered by the internet, but the excessive use of it will cause an adverse impact on human health. Internet addiction that occurs from excessive internet use is closely related to mental health disorders such as depression. Objective: To analyze the correlation between internet addiction levels with degree of depression on preclinical students Faculty of Medicine. Methods: This study was an observational analytic study with a cross sectional design conducted on preclinical students Faculty of Medicine Nusa Cendana University by filling in the Young's Internet Addiction Test (YIAT) questionnaire and the Patient Health Questionnaire–9 (PHQ-9). The sampling technique used purposive sampling with 80 respondents who met the inclusion and exclusion criteria. The study was analyzed univariately, and bivariately using Spearman test. Results: It was found that from 80 respondents there were 25 respondents (31.3%) with mild internet addiction, 51 respondents (63.8%) with moderate internet addiction, and 4 respondents (5.0%) with severe internet addiction. And from 80 respondents observed, 41 respondents (51.3%) experienced mild depression, 13 respondents (16.3%) experienced moderate depression, 4 respondents (5.0%) experienced severe depression, and 22 respondents (27.5%) were not depressed. The results of the bivariate analysis test in this study obtained p value = 0.000 (p <0.05). Conclusion: There is a significant and a strong correlation between internet addiction levels with degree of depression, which indicates that the higher the level of internet addiction the higher the degree of depression on preclinical students Faculty of Medicine class of 2017, 2018, and 2019.